2015
DOI: 10.1371/journal.pone.0118157
|View full text |Cite
|
Sign up to set email alerts
|

HIV Status Disclosure to Sexual Partners, among People Living with HIV and AIDS on Antiretroviral Therapy at Sokodé Regional Hospital, Togo

Abstract: BackgroundMany studies have reported factors associated with HIV status disclosure among People Living With HIV and AIDS (PLWHA) but very few were conducted among PLWHA receiving ART. In Togo, no study on HIV status disclosure to sexual partners has been conducted among PLWHA on ART yet. We sought to document factors associated with HIV status disclosure among PLWHA receiving ART at Sokodé regional hospital in Togo.MethodThis was a cross-sectional study conducted from May to July 2013 at the regional hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 19 publications
5
25
1
Order By: Relevance
“…In the present study, the relatively low level of disclosure of HIV status among the respondents was similarly observed in some studies across Africa; Mali, Burkina Faso, Uganda, Zimbabwe, Togo and Nigeria [32][33][34][35][36]. On the other hand, there were other studies in Ethiopia and Uganda that reported relatively high disclosure rates [4,8,19].…”
Section: *Significantsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, the relatively low level of disclosure of HIV status among the respondents was similarly observed in some studies across Africa; Mali, Burkina Faso, Uganda, Zimbabwe, Togo and Nigeria [32][33][34][35][36]. On the other hand, there were other studies in Ethiopia and Uganda that reported relatively high disclosure rates [4,8,19].…”
Section: *Significantsupporting
confidence: 84%
“…These determinants were; being in an older age group [32,40,41], married [5,16,27,35,38,41], not religious [42] having a higher level of education [32,38,41,43] and residing in an urban or semi-urban place [43]. Notwithstanding, some of these socio-demographic determinants for disclosure were on the contrary, not also observed in other studies such as; being in an older age group [5,35], being married [33,40], not religious [32], level of education [5,35,40], occupation [40,41], lower level of income [41] and residing in an urban or semi-urban place [35]. Therefore, it can be further observed that these relationships with disclosure appear to vary within and across studies which is probably due to the influence of a number of peculiar factors and circumstances that motivate disclosure such as the target of disclosure, HIV care and also, the enabling social and environmental conditions that exists.…”
Section: *Significantmentioning
confidence: 99%
“…Respondents who knew their sexual partner's HIV status were about 2.7 times more likely to disclose their HIV status to their partner as compared to those who did not know their partner's HIV status. This is also in line with other studies conducted in Bale Zone Hospital, Woldia hospital, Kemissie health center in Ethiopia (12,14,18) and in Ogun State in Nigeria and in Togo regional hospital (24,25). Because of aware of sexual partner's HIV positive status may encourage partners to disclosure for the purpose of preventing HIV transmission and to support each other.…”
Section: Discussionsupporting
confidence: 88%
“…When we goes to ART medication adherence, HIV positive status disclosure to sexual partner was 3.2 times more likely among respondents who had good ART medication adherence than poor ART medication adherence status. This finding is similar to a study done in Togo (24). This might be respondents may receive information continually and encouragement for caregivers to create favorable psychological conditions to disclose their HIV sero-positive status to their sexual partners.…”
Section: Discussionsupporting
confidence: 88%
“…15 A rate of 60.9% to sexual partners was reported in Togo. 16 In Tanzania, Yonah et al indicated that the overall prevalence of the serostatus disclosure stood at 93.3%. 17 Another cross-sectional study done in Nigeria concluded a disclosure rate of 95.0%.…”
Section: Discussionmentioning
confidence: 99%